Pemanfaatan Lahan kosong untuk Meningkatkan Aktivitas Belajar Anak Usia Dini dalam Sentra Alam di TK Aisyiyah Bustanul Athfal 50 Surabaya - Clarissa Qurrotu'Ainii; Salsabila Nur Azizah; Zida Fardasyah; Ratna Pangastuti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve early childhood learning activities by utilizing vacant land as a nature center at Aisyiyah Bustanul Athfal 50 Kindergarten, Surabaya. The underlying problem is the lack of variety in early childhood learning, which tends to be limited to the classroom and the suboptimal use of the surrounding environment as a learning resource. This study used a qualitative approach with the Classroom Action Research (CAR) method, conducted in two cycles. The subjects were 15 children in Group B, characterized by active learning but limited focus on learning and environmental exploration. Data were collected through observation, interviews, and documentation, while data validity was tested through triangulation of sources and techniques. The results showed that children's learning activities increased significantly after the implementation of nature-center-based learning. Children became more active, enthusiastic, and were able to interact better with their environment and peers. Activities such as planting, watering, observing insects, and maintaining garden cleanliness provided meaningful and enjoyable learning experiences. In addition, the utilization of vacant land was an effective solution in creating a contextual and child-friendly learning atmosphere. The environment around the school was optimally utilized as a learning medium appropriate to the development of early childhood. This study concluded that the nature center significantly contributed to increasing children's learning activities. Therefore, this nature-based learning model can be recommended as an innovation in early childhood learning for other educational units.